Efficacy and safety of dexmedetomidine in maintaining hemodynamic stability in pediatric cardiac surgery: a systematic review and meta-analysis - Qing Wang; Chuikai Chen; Li Wang (Elsevier, 2022)
Objectives: Dexmedetomidine (DEX) is a highly selective alpha-2 adrenergic receptor agonist, which is the main sedative in the intensive care unit. This study aims to investigate the effectiveness and adverse events of DEX in maintaining hemodynamic stability in pediatric cardiac surgery. Sources: Databases such as PubMed, Cochrane, Web of Science, WANFANG STATA and China National Knowledge Infrastructure were searched for articles about the application of DEX in maintaining hemodynamic stability during and after pediatric cardiac surgery up to 18th Feb. 2021. Only randomized controlled trials were included and random-effects model meta-analysis was applied to calculate the standardized mean deviation (SMD), odds ratio (OR) and 95% confidence interval (CI). Summary of the findings: Fifteen articles were included for this meta-analysis, and 9 articles for qualitative analysis. The results showed that preoperative prophylaxis and postoperative recovery of DEX in pediatric patients undergoing cardiac surgery were effective in maintaining systolic blood pressure (SBP), mean arterial pressure (MAP), diastolic blood pressure (DBP) and reducing heart rate (HR) (SBP: SMD = -0.35,95% CI: -0.72, 0.01; MAP: SMD = -0.83, 95% CI: -1.87,0.21; DBP: SMD = -0.79,95% CI: -1.66,0.08; HR: SMD = -1.71,95% CI: -2.29, -1.13). In addition, the frequency of Junctional Ectopic Tachycardia in the DEX treatment group was lower than that in the placebo group. Conclusions: The application of DEX for preoperative prophylaxis and postoperative recovery in pediatric cardiac surgery patients are effective in maintaining hemodynamic stability, and the clinical dose of DEX is not significantly related to the occurrence of pediatric adverse events which may be related to individual differences.